Transformasi Pemberdayaan Ekonomi Perempuan : Strategi Pemberdayaan Kelompok Wanita Tani Berbasis Ekonomi Islam di Desa Sri Bandung, Banyuasin - Kahfi, Al; Oktaviani, Yeyen; Fadilah, Nurul; Mahmudi, Ilham (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2024)
This study aims to analyze and determine the impact of women's economicempowerment on family welfare in the perspective of sharia economics (a studyof the women's farming group movement (KWT) in the village of Sri Bandung,Banyuasin, South Sumatra. The analytical method used in this study is aqualitative method with data collection techniques in the form of interviews, documentation and from several sources Journals, other articles From the research. that has been carried out, it was found that the existence of the women farmer group movement was able to empower the people in the village of Sri Bandung by utilizing the potential in the area Also, being able to become an attraction for young people in learning in terms of agricultural management. Women's activities in helping the family economy by working as rubber farm laborers, teachers, and women's farming groups also become a byproduct of Islamic economic values. Women and men have the same rights to work and improve the family economy and achieve the goal of becoming a prosperousfamily